Investigating behaviour of reinforced concrete with glass fibre - Alsadey, Salahaldein; Abdallateef, Miftah; Mohamed, Muftah; Milad, Abdalrhman (Penerbit Universiti Kebangsaan Malaysia, 2021)
Concrete is the most commonly used building material. Nowadays, the world has seen the construction of engineering applications that has become difficult and complicated. Therefore, it is important to have high strength and adequate workability. Besides that, the glass fibre is highly beneficial as a construction material for reinforced concrete as it can be identified as one of the numerous compelling topics related to its benefits. This study contributes to the specification and classification of glass fibre reinforced concrete (GFRC). However, ordinary concrete has limited ductility, slight resistance to cracking, and insufficient tensile strength. Internal micro-cracks in the concrete are visible, and the proliferation of such micro-cracks caused its weak tensile strength. When a certain percentage of fibre is added to the concrete, it improves the properties of the strain, namely, resistance to cracking, ductility, toughness, and flexure strength. The current paper outlines the experimental study conducted on the usage of glass fibre with structural concrete. The parameters were used in percentages, which varied from 0.5% to 2% by weight of cement in concrete, and the properties of the FRC (fibre reinforced concrete), such as ultrasonic pulse velocity test, flexure strength, and compressive strength were examined. However, it refers to an increase in deformation before failure of the structural concrete, reinforced with a high ratio of GFR. The results show good performance of concretes containing glass fibre and increasing glass fibre content, increasing the compressive strength.